Distribusi Cacing Trematoda Saluran Pencernaan Katak Dari Berbabgai Lokasi Persawahan Di Kabupaten Lombok Timur - Wolagole, Kristian; Kholik, Kholik; Supriadi, Supriadi; Oktaviana, Dina (Mandalika Veterinary Journal, 2021)
Trematode worms have been found in various types of frogs which cause disease in frogs or toads can be a reservoir for these worms. Lombok Island has many rice fields which are habitat for frogs. Frogs that live in this environment allow direct contact with various types of Trematodes. The purpose of this study was to determine the type and distribution of Trematoda worms found in the digestive tract of frogs in the rice fields of East Lombok Regency. A cross-sectional survey study using purposive sampling methods on frogs in three rice fields in East Lombok Regency was carried out in February 2020. Worms were collected from the digestive tract of frogs and fixed with 70% warm alcohol, cleaned with alcohol, and examined under a microscope. A total of 64 frog samples were taken in three rice fields, East Lombok Regency. A sample examination was carried outÂ  at the Equin Clinical Center Skill laboratory Faculty of Veterinary Medicine of Mandalika University of Education. The results showed that Mesocoelium spp was distributed among frogs in three rice fields in East Lombok Regency, with a prevalence of 45% in Pringgabaya Village, 50% in Suele Village, and 53.57% in Tanjung Teros Village.